2011
DOI: 10.1172/jci59353
|View full text |Cite
|
Sign up to set email alerts
|

Mouse model of enlarged vestibular aqueducts defines temporal requirement of Slc26a4 expression for hearing acquisition

Abstract: Mutations in human SLC26A4 are a common cause of hearing loss associated with enlarged vestibular aqueducts (EVA). SLC26A4 encodes pendrin, an anion-base exchanger expressed in inner ear epithelial cells that secretes HCO 3 -into endolymph. Studies of Slc26a4-null mice indicate that pendrin is essential for inner ear development, but have not revealed whether pendrin is specifically necessary for homeostasis. Slc26a4-null mice are profoundly deaf, with severe inner ear malformations and degenerative changes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(145 citation statements)
references
References 37 publications
5
137
1
2
Order By: Relevance
“…In the vestibular apparatus, pendrin is expressed in nonsensory epithelial cells surrounding sensory hair-cell patches in the saccule, utricle, and ampulla, and in a subset of cells of the endolymphatic sac terminating the vestibular aqueduct [5]. Lack of pendrinmediated Cl -/HCO 3 -exchange in the inner ear acidifies endolymph, thus promoting loss of the endocochlear potential and elevating endolymph [Ca 2+ ] [6,7], and likely contributes to enlargement of the cochlear lumen [8] and vestibular aqueduct through reduced volume absorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the vestibular apparatus, pendrin is expressed in nonsensory epithelial cells surrounding sensory hair-cell patches in the saccule, utricle, and ampulla, and in a subset of cells of the endolymphatic sac terminating the vestibular aqueduct [5]. Lack of pendrinmediated Cl -/HCO 3 -exchange in the inner ear acidifies endolymph, thus promoting loss of the endocochlear potential and elevating endolymph [Ca 2+ ] [6,7], and likely contributes to enlargement of the cochlear lumen [8] and vestibular aqueduct through reduced volume absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of pendrinmediated Cl -/HCO 3 -exchange in the inner ear acidifies endolymph, thus promoting loss of the endocochlear potential and elevating endolymph [Ca 2+ ] [6,7], and likely contributes to enlargement of the cochlear lumen [8] and vestibular aqueduct through reduced volume absorption. Development of normal hearing in the mouse requires pendrin expression between e16.5 and p2 of embryonic and neonatal developent [5].…”
Section: Introductionmentioning
confidence: 99%
“…Pendrin is expressed in several locations of the cochlea and the vestibule of the mouse inner ear [38,39]. This expression pattern involves regions important for endolymphatic fluid resorption, consistent with pendrin's essential role in the normal development and proper function of the inner ear [38].…”
Section: Pendrin In the Inner Earmentioning
confidence: 62%
“…However, recently, transgenic mice with Slc26a4 expression inducible by doxycycline on a background of mice lacking endogenous pendrin expression were generated. It was demonstrated that expression of pendrin at early embryonic stages of E0-E17.5 was necessary and sufficient to restore normal hearing in Tg[E];Tg[R];Slc26a4 ∆ / ∆ mice (Choi et al, 2011). Ablating expression of Slc26A4 at this critical time results in complete or partial hearing loss in these mice, recapitatulating the phenotypes documented for many patients with mutations in SLC26A4 (Choi et al, 2011).…”
Section: Slc26a4 (Dfnb4/pds)mentioning
confidence: 88%